The representation of foreign culture in English textbooks used in Cambodian upper secondary schools - Seth Soy; Safnil Safnil; Syafryadin Syafryadin (Universitas Islam Sultan Agung, 2023)
It is generally recognized that the representation of foreign culture in textbooks is pivotal for effective language learning, and successful cross-cultural communication. With this regard, the present study investigates the representation of foreign culture in English textbooks used in Cambodian upper secondary schools. The current study employs content analysis (CA) approach to analyze three English textbooks used in Cambodian upper secondary schools. Three different frameworks were used as the checklists. To investigate how foreign culture is introduced, and the proportion of subcategories in culture introduction, the framework of Zu and Kong (2009) was employed. The researchers also used the framework of Cortazzi and Jin (1999) to see the percentage of the target culture and international culture within the cultural categories. The last framework is the one proposed by Yuen (2011), which was applied to measure the distribution of cultural elements. The findings show that all two approaches to culture introduction namely direct and indirect introduction are included, but the direct introduction is predominant (61%). For the direct introduction, among four subcategories, the highest proportion is on Texts Depicting Cultural Events (51%) followed respectively by Situational Dialogues (30%), Words Accompanied by Pictures (14%), and Cultural Notes (5%). For the indirect introduction, between two subcategories, Cognitive Approach (80%) is dominant over Behavioural and Affective Approach (20%). Furthermore, regardless of source culture, target culture (66%) covers predominantly in the textbooks compared to international culture (34%). Related to cultural elements, Products account for 74% followed by Practices 13%, Persons 12%, and Perspectives 1%. The results suggest that textbook developers should consider the appropriate proportion of these cultural components, and English teachers should exploit the importance of these cultural contents in their teaching.